Comparison of flow regimes on biocorrosion of steel pipe weldments: Community composition and diversity of biofilms. (September 2019) - Liduino, Vitor Silva; Cravo-Laureau, Cristiana; Noel, Cyril; Carbon, Anne; Duran, Robert; Lutterbach, Marcia Teresa; Camporese Sérvulo, Eliana Flávia
Abstract: Worldwide, the corrosion of petroleum pipelines is the cause of severe operational failures and damages to the environment, and the majority of them may have been intensified by microbial activities. However, few scientific publications have investigated the influence of seawater with indigenous microorganisms in internal corrosion of welded joints in long-distance pipelines, which has motivated this study. Here, a combination of culture-based and molecular microbiological methods was applied to measure the microbial abundance, diversity and composition of biofilms formed on two corroded weldments (gas tungsten arc - GTAW and shielded metal arc - SMAW) of an API 5L X65 microalloyed steel under laminar and turbulent flow regimes using seawater from Guanabara Bay (Rio de Janeiro, Brazil). Overall, turbulent flow did not reduce the biomass of sessile microorganisms on welded joints compared to laminar flow. Phylogenetic analysis revealed that the Proteobacteria, Firmicutes and Bacteroidetes were the dominant phyla in biofilms attached to GTAW and SMAW joints. At the genus level, all samples showed similar microbial composition with dominance of Desulfovibrio . However, analysis at OTU level revealed that there were specific microorganisms in each corrosive sample, even though they were affiliated to sulfate-reducers. Thus, microbial community compositions were influenced by type of weld, flow regime and biofilm age. The results of our study will be of benefit to the further studies of weld biocorrosion and biofilm ecology within pipelines. Graphical abstract: Image 1 Highlights: Characterization of biofilms development on welded joints exposed to laminar and turbulent flows. Turbulent flow did not reduce the number of sessile microorganisms on welded joints. Both fluid flow regime and type of weld influenced the microbial composition at OTU level. Oxygen and sulfide concentrations in the fluid driven the assembly of the microbial communities. Corrosion rate was more severe in welded joints exposed to laminar flow regime.